2020
DOI: 10.1097/anc.0000000000000644
|View full text |Cite|
|
Sign up to set email alerts
|

Improving the Efficiency and Effectiveness of Parent Education in the Neonatal Intensive Care Unit

Abstract: Background: March of Dimes partners with hospitals across the country to implement NICU Family Support (NFS) Core Curriculum, a program providing education to parents in neonatal intensive care units (NICUs) across the country. Purpose: This NFS project's goal was to increase the efficiency and effectiveness of NICU parent education by establishing consistency, improving quality, and identifying best practices. Methods/Search Strategy: A 5 topic curriculum was developed and implemented across NFS program sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…For example, cameras in the NICU have been shown to reduce stress levels in parents related to separation from their infant(s; Guttmann et al, 2020). Providing education in a high stress situation is challenging and providing consistent messaging and materials has been shown to be key (Gehl et al, 2020). Therefore, the use of eHealth platforms, such as the existing eHealth educational platform called Chez NICU Home which was developed prior to the pandemic, was invaluable as it allowed family members who could not be present in to NICU to remain engaged in their infant's care and receive all the education.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cameras in the NICU have been shown to reduce stress levels in parents related to separation from their infant(s; Guttmann et al, 2020). Providing education in a high stress situation is challenging and providing consistent messaging and materials has been shown to be key (Gehl et al, 2020). Therefore, the use of eHealth platforms, such as the existing eHealth educational platform called Chez NICU Home which was developed prior to the pandemic, was invaluable as it allowed family members who could not be present in to NICU to remain engaged in their infant's care and receive all the education.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization is the premise of education. The NICU Family Support (NFS) Core Curriculum, a standardized education program, was implemented for parents of infants in NICUs; the project found that, among 3,648 attendees at 41 sites across the country, 77% of them reported learning “a lot” and 85% reported boosted confidence, with higher satisfaction and a positive knowledge change [ 45 ]. Similarly, another study also found consistent information provided through standardized discharge tools could alleviate parents’ mental stress and build up their confidence [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essas atividades, comumente, são realizadas por enfermeiros, médicos, terapeutas ou gerentes e englobam conteúdos como amamentação, cuidado canguru, preparo dos pais para a primeira visita, comunicação e compartilhamento de informações e planejamento da alta. 25 Outro estudo indica que a relação e aproximação das mães das crianças internadas na UTIN com os profissionais do setor trazem benefícios, como diminuir os impactos negativos que estes causam para si, bem como menores níveis de estresse e angústia de mães, ressaltando a importância de uma equipe multiprofissional integrada e humanizada e que favorece o processo comunicativo. 23 Dessa forma, o atributo da relação precoce mãe/família/criança pode ampliar ou abrandar o impacto eventualmente negativo do nascimento da criança prematura, especialmente quanto ao desenvolvimento e crescimento, visto que a família enfrenta uma série de obstáculos que eram inesperados para ela, como o risco da morte da criança, a dificuldade no contato pele a pele, o impasse de iniciar relação afetiva entre ambos e inadequações na realização do papel materno, paterno e familiar à criança na UTIN.…”
Section: Discussionunclassified
“…Estudo aponta que o vínculo materno com a criança prematura pode ser promovido por meio de diferentes métodos, como a flexibilização das visitas na UTIN, a realização do método Canguru desde a UTIN até o ambiente domiciliar que, por sua vez, estimula o crescimento e o desenvolvimento motor e cognitivo de crianças prematuras, favorece a amamentação, o fortalecimento da relação afetiva família/criança prematura, permite aos pais maior participação nos cuidados neonatais, aquisição de competência e confiança no cuidado com o filho e redução do estresse e da dor do recém-nascido prematuro. 25 Nesse sentido, a teoria do apego, desenvolvida por Bowlby, pode ser útil para entender como os familiares apreendem experiências e constroem o vínculo. A ideia de vínculo se refere à percepção de confiança e segurança, as quais estão intimamente ligadas à imagem do afeto.…”
Section: Discussionunclassified